ANALISIS PENGARUH PEMASARAN INTERNAL TERHADAP KUALITAS PELAYANAN DI RSUD H. PADJONGA DAEN NGALLE TAKALAR TAHUN 2022 - Khusnul Khotimah; Dian Ekawaty; Darmawati Junus; Ryryrn Suryaman Prana Putra (Institut Kesehatan Pelamonia, 2024)
Internal marketing is an activity of attracting, developing, motivating and retaining qualified employees. The problem in the study is that the decrease in the number of inpatient and outpatient visits can identify whether so far the quality of services provided, including the performance or behavior of health workers to the service user community is not good, causing patient dissatisfaction. The purpose of this study is to find out the influence of internal marketing on the quality of service atH. Padjonga Daeng Ngalle Hospital, Takalar Regency 2022. The type of research used in this study is quantitative descriptive research with a cross-sectional study approach. The sampling technique used was Purposive Sampling with a total sample of 183 employees and 183 patients. This study used univariate and bivariate data analysis. The results of this study show that there is no effect of training (p= 0.757), work environment (p= 0.313), reward (p= 0.832), job satisfaction (p= 1) on service quality while motivation (p= 0.045) affects the quality of service at H. Padjonga Daeng Ngalle Takalar Hospital in 2022. It is suggested to the H. Padjonga Daeng Ngalle Takalar Hospital that it is better to improve employee performance because the better the employee performance, the better the quality of service provided to patients.